Crucified upon metals and alphabets: alchemical iconography of the sixteenth-century illustrated treatises by Martin Sturtz - Sergei Zotov (BJHS Themes)
This paper addresses the links between alchemy, mining and religion in the early modern alchemical iconography of the German mining theorist Martin Sturtz. He created a special version of the prayer Vaterunser (Our Father) for miners and metallurgists and used the images from Christian and alchemical iconography to demonstrate the history of the creation of metals and how they grow inside the Earth. In one of his images, the Saviour is crucified against the background of coloured strips or stripes, symbolizing the seven metals inside a sedimentary complex. In another miniature, the blood spilling from his wound gives rise to ore veins in which metals ripen. These and the other iconographical and textual examples from Sturtz’s treatises show the attempt to connect the mining process with alchemical theory and Christian religion. This paper will shed light on the origins of this unusual alchemical imagery and its connection with other alchemical and theological works, especially those by Paul Lautensack.